Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.11648/j.ajls.s.2015030601.19
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Replacing Soybean Meal with Jojoba Meal in Sea Bream (Sparus aurata) Diets on Fish Performance

Abstract: Abstract:The study aimed to investigate the effect of replacing soybean meal (SBM) by treated, either by heat (HJM) or by boiling (BJM), Jojoba meal (JM), to eliminate the negative effects of antinutritional factors, at 10, 20 and 30% replacing levels in diets of sea bream (Sparus aurata)) fingerlings on growth performance, nutrient utilization, body biochemical composition, middle intestine morphology and measuring of some hematological parameters of sea bream. Results indicated an enhancement in growth and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
(18 reference statements)
2
1
2
Order By: Relevance
“…Similar results were reported by Abd El‐Rahman et al (), El‐Anany () who treated JM with isopropanol (70%), and Shamma et al () who found that the addition of JM in broiler diets resulted in beneficial effects on the blood lipids profile. The results disagreed with that recently reported by Saleh and Toutou () showing increase in the lipid contents as the JM inclusion increased. Serum total protein, albumin and globulin levels indicated no negative effects when soybean meal was partially replaced by JM (Saleh & Toutou, ).…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…Similar results were reported by Abd El‐Rahman et al (), El‐Anany () who treated JM with isopropanol (70%), and Shamma et al () who found that the addition of JM in broiler diets resulted in beneficial effects on the blood lipids profile. The results disagreed with that recently reported by Saleh and Toutou () showing increase in the lipid contents as the JM inclusion increased. Serum total protein, albumin and globulin levels indicated no negative effects when soybean meal was partially replaced by JM (Saleh & Toutou, ).…”
Section: Resultscontrasting
confidence: 99%
“…The results disagreed with that recently reported by Saleh and Toutou () showing increase in the lipid contents as the JM inclusion increased. Serum total protein, albumin and globulin levels indicated no negative effects when soybean meal was partially replaced by JM (Saleh & Toutou, ). The results indicated gradual decrease in TC levels coincided with the increase in TAG.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…However, the presence of antinutritional components (trypsin inhibitors, phytate, tannins, polyphenolic compounds, and simmondsin) obligates its detoxification before use (Golan‐goldhirsh et al, 2002; Medina & Trejo‐gonzalez, 1990; Verbiscar & Banigan, 1978). The jojoba meal content of tannins, expressed as tannic acid, was detected in various amounts (1.50% to 2.57%), while the total phenolic compounds and the phytate content were found to be 2.67% and 2.3%, respectively (Ngoupayou & Daniel, 1982; Saleh & Toutou, 2015). The hulls are composed mainly of fibers (15.6%), proteins (7%), carbohydrates, and ash (4.4%).…”
Section: Phytochemistrymentioning
confidence: 99%